2006
DOI: 10.1016/j.jsams.2006.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for injury in non-elite netball

Abstract: This paper identifies the risk and protective factors for injury in non-elite netball. Three-hundred and sixty-eight non-elite netballers completed a baseline questionnaire at the commencement of the 1997 preseason. Participants were telephoned each month during the 1997 and 1998 playing seasons to provide details of their exposure at training and games and any injury experiences in the previous 4 weeks. The incidence of injury in this study was 14 injuries per 1000 player hours. The risk factors for injury we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 22 publications
4
68
1
Order By: Relevance
“…This study high lighted an injury prevalence ranging from 55% at club level to 84% amongst national players with an injury rate of 1.9 injuries per player over one netball season. This injury rate is higher (1.1) than that compared to the study by Hume and Steele (2000) but lower (2.6) than the study by McManus, Stevenson and Finch (2006).…”
Section: Discussioncontrasting
confidence: 64%
“…This study high lighted an injury prevalence ranging from 55% at club level to 84% amongst national players with an injury rate of 1.9 injuries per player over one netball season. This injury rate is higher (1.1) than that compared to the study by Hume and Steele (2000) but lower (2.6) than the study by McManus, Stevenson and Finch (2006).…”
Section: Discussioncontrasting
confidence: 64%
“…During tournament games 238 injuries were observed per 1000 playing hours (Hume & Steele, 2000), Saunders and Otago (2009) further documented from three seasons of competition that injury rates range from 66.7 to 71.4 per 1000 participants. These analyses have shown that the majority of injuries are chronic in nature and occur predominantly in the lower extremities (McManus, Stevenson, & Finch, 2006). The knee has been shown to be the most commonly injured musculoskeletal structure in netball players, accounting for 24% of total injuries (Hopper, 1997;Hume & Steele, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…6 Similarly, within a cohort of community netball players, 32% of total body injuries involved the ankle. 7 A single history of ankle sprain predisposes the same ankle to recurrent damage, 8 especially in the case of improper rehabilitation and premature return to play. Mechanical changes to the ankle joint complex often become evident following an acute ankle sprain, as do perceived limitations such as feelings of instability and sensations of 'giving way'.…”
Section: Introductionmentioning
confidence: 99%